Answer:
1st option
Step-by-step explanation:
10 + 12 ← factor out 2 ( the GCF of 10 and 12 ) from each term
= 2(5 + 6)
Answer:
4x + 1
Step-by-step explanation:
Multiply f + g by x because f + g is in parenthesis:
f(x) + g(x)
Then implement equation #1 for f(x) into our equation:
3x - 1 + g(x)
Then implement the other equation for g(x) into our equation:
3x - 1 + x + 2
Then switch the positions of -1 and +x:
3x + x - 1 + 2
Simmplify:
4x + 1
Pls consider giving my answer the Brainliest! Because it would help and mean a lot! ; )
Answer: Positive (but not sure)
Step-by-step explanation: Are there answers to the questions is so i could help more but if correct hope i helped :)
K=4
add seven on both sides
2x-4y=7
add 4y on both sides
2x=7+4y
divide 2 on both sides
x=7+4y/2
plug that into original equation
2(7+4y/2)-4y-7=0
7 and 4y cancel out
2(2)=0
4=0
Answer:
Step-by-step explanation:
Alright so we are going to solve
5x ≥ 25 Divide both sides by 5
x≥5